1980
DOI: 10.4267/2042/65541
|View full text |Cite
|
Sign up to set email alerts
|

Premier isolement en France du virus de l'influenza du porc (Hsw1N1) dans un environnement pathologique plurimicrobien

Abstract: Au cours d'un épisode pathologique ayant sévi dans une exploitation de porcs, il a pu être isolé, pour la première fois en France, un virus influenza du porc Hsw1N1, accompagné d'une flore microbienne pathogène. Le virus ne s'est pas transmis à l'homme et l’origine du contage est restée inconnue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 1980, the swine influenza virus H1N1 (SwH1N1) was isolated for the first time in France from pigs presenting multimicrobial conditions [13,14]. A sero-epidemiological investigation initiated in 198t showed that the virus had spread across the French territory [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In 1980, the swine influenza virus H1N1 (SwH1N1) was isolated for the first time in France from pigs presenting multimicrobial conditions [13,14]. A sero-epidemiological investigation initiated in 198t showed that the virus had spread across the French territory [11,12].…”
Section: Introductionmentioning
confidence: 99%